2019
DOI: 10.1521/pedi_2019_33_455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Thresholds for Criterion A in the Alternative DSM-5 Model for Personality Disorders

Abstract: The Level of Personality Functioning Scale (LPFS) of the Alternative DSM-5 Model for Personality Disorders (AMPD) was formulated to assess the presence and severity of personality disorders (PDs). Moderate impairment (Level 2) in personality functioning, as measured by the LPFS, was incorporated into the AMPD as a diagnostic threshold for PD in Criterion A of the general criteria, as well as for the "any two areas present" rule for assigning a specific PD diagnosis. This study represents the first evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…The result that mentalizing fully mediated the relationship between BPD severity and interpersonal functioning confirmed our hypothesis and is in line with prior research on the relationship between both personality functioning and mentalizing (31,61) as well as personality pathology and personality functioning (22)(23)(24)(25). Further, this result is in line with the mentalizing theory according to which mentalizing concerns the apprehension and interpretation of interpersonal interaction and, therefore, has a key function in constructive and meaningful interpersonal functioning (62).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result that mentalizing fully mediated the relationship between BPD severity and interpersonal functioning confirmed our hypothesis and is in line with prior research on the relationship between both personality functioning and mentalizing (31,61) as well as personality pathology and personality functioning (22)(23)(24)(25). Further, this result is in line with the mentalizing theory according to which mentalizing concerns the apprehension and interpretation of interpersonal interaction and, therefore, has a key function in constructive and meaningful interpersonal functioning (62).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, a PD is assessed by rating its severity on a continuum ranging from normal (healthy) personality functioning through mild and moderate to severe personality pathology. The link between personality pathology and personality functioning has previously been described thoroughly in the literature (19)(20)(21) and has been supported empirically (22)(23)(24)(25), emphasizing the relevance of impaired personality functioning as a measure of the severity of personality pathology.…”
Section: Introductionmentioning
confidence: 76%
“…Buer Christensen et al ( 2020) found a mean LPFS score for BPD with comorbid PDs of 2.67 (SD = .64), which is consistent with our findings for BPD (M = 2.72; SD = .25). Buer Christensen et al also reported means for the domains of BPD: Identity 2.81 (SD = .78), Self-Direction 2.24 (SD = .91), Empathy 2.91 (SD = .57), and Intimacy 2.72 (SD = .73;Buer Christensen et al, 2020), which are close to our findings. For SPD without comorbid PDs, they reported a mean LPFS of only 1.72 (SD = 1.56), which seems low considering that LPFS operationalizes the levels and subdomains by using prototypical descriptions, where BPD is in Level 3 (severe impairment) and SPD is in Level 4 (extreme impairment).…”
Section: Criterion a In The Borderline Conditionssupporting
confidence: 91%
“…Only a few studies have used the AMPD Module I interview (Buer Christensen et al, 2018, 2020; Kampe et al, 2018). Buer Christensen et al (2020) found a mean LPFS score for BPD with comorbid PDs of 2.67 ( SD = .64), which is consistent with our findings for BPD ( M = 2.72; SD = .25). Buer Christensen et al also reported means for the domains of BPD: Identity 2.81 ( SD = .78), Self-Direction 2.24 ( SD = .91), Empathy 2.91 ( SD = .57), and Intimacy 2.72 ( SD = .73; Buer Christensen et al, 2020), which are close to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nine participants from the research project, “An Examination of the DSM‐5 Level of Personality Functioning Scale in a Representative Clinical Sample” (Buer Christensen et al, 2020; Buer Christensen et al, 2019; Buer Christensen et al, 2018), who had agreed to be contacted at a later stage for additional research purposes, were approached by the first author (A). They received written information about the research via their therapists.…”
Section: Methodsmentioning
confidence: 99%